MAIN DIRECTIONS OF ENVIRONMENTAL POLICY OF THE REPUBLIC OF UZBEKISTAN - Pulatov Madaminjan Muhammadjon ugli; Qasimov Sirajiddin (Journals Park Publishing, 2022)
This article discusses the need to switch to industrial and agricultural, economic technology that saves natural resources when storing biosphere, technology without waste, technology that works in closed cycles.
Keywords: ecology; biosphere; natural resource